A New Centennial Sea‐Level Record for Antalya, Eastern Mediterranean. Issue 7 (2nd July 2018) - Ozturk, U.; Marwan, N.; von Specht, S.; Korup, O.; Jensen, J.
Abstract: Quantitative estimates of sea‐level rise in the Mediterranean Basin become increasingly accurate thanks to detailed satellite monitoring. However, such measuring campaigns cover several years to decades, while longer‐term sea‐level records are rare for the Mediterranean. We used a data archeological approach to reanalyze monthly mean sea‐level data of the Antalya‐I (1935–1977) tide gauge to fill this gap. We checked the accuracy and reliability of these data before merging them with the more recent records of the Antalya‐II (1985–2009) tide gauge, accounting for an eight‐year hiatus. We obtain a composite time series of monthly and annual mean sea levels spanning some 75 years, providing the longest record for the eastern Mediterranean Basin, and thus an essential tool for studying the region's recent sea‐level trends. We estimate a relative mean sea‐level rise of 2.2 ± 0.5 mm/year between 1935 and 2008, with an annual variability (expressed here as the standard deviation of the residuals, σ residuals  = 41.4 mm) above that at the closest tide gauges (e.g., Thessaloniki, Greece, σ residuals  = 29.0 mm). Relative sea‐level rise accelerated to 6.0 ± 1.5 mm/year at Antalya‐II; we attribute roughly half of this rate (~3.6 mm/year) to tectonic crustal motion and anthropogenic land subsidence. Our study highlights the value of data archeology for recovering and integrating historic tide gauge data for long‐term sea‐level and climate studies. Plain Language Summary: We demonstrate how data archeology of tide gauge data contributes to completing the contemporary century sea‐level record in the eastern Mediterranean Basin. It is important to rescue such data and to make them available for future research on sea‐level rise that goes beyond modern and highly accurate satellite‐based monitoring. In our particular case, the monthly mean sea‐level records of Antalya‐I (1935–1977), we merged them with the modern records of Antalya‐II (1985‐2009) located only ~5 km away. This merger offers a homogeneous composite time series of monthly and annual mean sea level of nearly 75 years, the longest record in the eastern Mediterranean Basin. We reviewed all previous work, metadata, and changes in the zero of tide gauges and datum. Major issues included obtaining the leveling information and to determine rates of tectonic vertical crustal movement. It is worth noting that nearly half of the observed sea‐level rise in Antalya‐II is driven by local vertical land motion, which might be influenced heavily by anthropogenic sources. Key Points: We reconstructed the longest tide gauge record for the eastern Mediterranean Sea The merger offers ~75 years of composite and quality‐checked tide gauge data in Antalya, Turkey Relative mean sea‐level rise at Antalya was 2.2 ± 0.5 mm/year (1935–2008) and 6.0 ± 1.5 mm/year (1985–2008)